Association between duration of electronic screen use for non-educational purposes and depression symptoms among middle and high school students: a cross-sectional study in Zhejiang Province, China - Wang, Hao; Bragg, Fiona; Guan, Yunqi; Zhong, Jieming; Li, Na; Pan, Jin; Yu, Min (Frontiers in Public Health, 2023)
Background: Mental disorders are recognized as leading causes of disease burden. Existing literature on the association of electronic screen duration with depression among adolescents was contradictory. The current study aimed to elucidate the association between duration of electronic screen with non-educational purposes and depression symptoms among middle and high school students in Zhejiang Province, China. Methods: A cross-sectional study of 27 070 students in grades 7-12 from 376 middle and high schools was conducted through an anonymous self-administered questionnaire between April and June 2022. Poisson regression was utilized to appraise the association between electronic screen duration with non-educational purposes and depression symptoms. Results: Of the 27 006 eligible students, 51.6% (13 932) were boys. The mean age was 15.6±1.7 years. The overall prevalence (95%CI) of depression symptoms was 22.4% (21.4-23.4). Girls (27.6%, 95%CI: 26.2-29.0) have higher prevalence of depression symptoms than boys (17.7%, 95%CI: 16.7-18.8). After adjustment for socio-demographic status, behavioral lifestyle, self-perceived health, academic performance, loneliness and sadness, compared to those who without being exposed to electronic screen with non-educational purposes, the PRs (95%CI) for depression symptoms was 1.03 (1.02-1.04), 1.07 (1.05-1.09), 1.10 (1.07-1.13), 1.14 (1.10-1.18), 1.18 (1.12-1.23), and 1.21 (1.15-1.29), respectively, for those exposed to electronic screen with non-educational purposes <1 hours/day, 1 hour/day, 2 hours/day, 3 hours/day, 4 hours/day, and ≥5 hours/day. Conclusion: Duration of electronic screen with non-educational purposes is positively associated with depression symptoms among middle and high school students, even though daily short-duration exposure.